Study of the possibility for chrome separation and concentration from waste - water by Lewatit S 1080 and Wofatit KPS - Petrovska - Jovanović, Simka; Stojanova, Kornelija; Miloševska, Ratka (Macedonian Journal of Ecology and Environment, 1994)
Synthetic ion-exchangers are especially interesting and in our days they have privilege in comparison with the other methods for the ions separation. So, the possibility for Cr(III) and Cr(VI) separation and concentration from waste-water by means of Lewatit S1080 and Wofatit KPS has been studied. On purpose to find the optimal conditions out, many investigations for the dependence on pH solution flowing through the ionexchangers column and eluent concentration being applied, have been made. The quantitative determinations have been made by means of spectrophotometric method. The obtained results point out that those ion-exchangers can be successfully used for waste-water where their concentration is too small (waste water of lead and zinc mine , Sasa„).